Intestinal permeability in patients with Crohn's disease and ulcerative colitis and their first degree relatives. Issue 1 (January 1994) - Munkholm, P; Langholz, E; Hollander, D; Thornberg, K; Orholm, M; Katz, K D; Binder, V
Abstract : Increased intestinal permeability in patients with Crohn's disease and their first degree relatives has been proposed as an aetiological factor. The nine hour overnight urinary excretion of polyethyleneglycol-400 (PEG-400) and three inert sugars (lactulose, l-rhamnose, and mannitol) was used to test the permeation in 47 patients with Crohn's disease of whom 18 had at least one first degree relative with inflammatory bowel disease (2BD) and 52 patients with ulcerative colitis of whom 16 had at least one first degree relative with IBD. A total of 17 first degree relatives with IBD and 56 healthy first degree relatives were included. Thirty one healthy subjects not related to patients with IBD served as controls. No significant differences in PEG-400 permeation were found between the groups of patients, relatives, and controls, or between diseased and healthy relatives. The permeability to lactulose, rhamnose, and mannitol similarly did not differ between the three groups. This study challenges the previously reported findings of increased PEG-400 permeation in patients with Crohn's disease and in their healthy and diseased first degree relatives. There was no increase in permeability in a similar group of ulcerative colitis patients and their families.